2008
DOI: 10.1093/aje/kwn068
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sequelae of Injury Mechanisms and Mild Traumatic Brain Injury Incurred during the Conflicts in Iraq and Afghanistan: Persistent Postconcussive Symptoms and Posttraumatic Stress Disorder

Abstract: A cross-sectional study of military personnel following deployment to conflicts in Iraq or Afghanistan ascertained histories of combat theater injury mechanisms and mild traumatic brain injury (TBI) and current prevalence of posttraumatic stress disorder (PTSD) and postconcussive symptoms. Associations among injuries, PTSD, and postconcussive symptoms were explored. In February 2005, a postal survey was sent to Iraq/Afghanistan veterans who had left combat theaters by September 2004 and lived in Maryland; Wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
454
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(497 citation statements)
references
References 33 publications
(42 reference statements)
38
454
3
2
Order By: Relevance
“…A substantial number of cross-sectional studies have shown higher (nearly double) rates of PTSD in individuals with mTBI, observed in both military (Hoge et al, 2008;Schneiderman et al, 2008;Luethcke et al, 2011;Vasterling et al, 2012;Rosenfeld et al, 2013) and civilian (Bryant et al, 2010;Mayou et al, 2000) settings. Moreover, these findings have been corroborated using prospective study designs in civilians (Roitman et al, 2013) and in active duty service members (Yurgil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of cross-sectional studies have shown higher (nearly double) rates of PTSD in individuals with mTBI, observed in both military (Hoge et al, 2008;Schneiderman et al, 2008;Luethcke et al, 2011;Vasterling et al, 2012;Rosenfeld et al, 2013) and civilian (Bryant et al, 2010;Mayou et al, 2000) settings. Moreover, these findings have been corroborated using prospective study designs in civilians (Roitman et al, 2013) and in active duty service members (Yurgil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal follow-up of military personnel initially evacuated to Longstuhl with mTBI (self-report of war-related brain injury event) showed that rates of disability 6-12 months after evacuation were high and outcomes worse, overall in those service members with mTBI, comparable to those of civilian cohorts or polytrauma patients with mTBI (MacDonald et al, 2014). MacDonald et al found no substantial differences in cognition between the evacuated personnel with and without a history of mTBI, however rates of PTSD and depression were higher in the mTBI group (MacDonald et al, 2014).A substantial number of cross-sectional studies have shown higher (nearly double) rates of PTSD in individuals with mTBI, observed in both military (Hoge et al, 2008;Schneiderman et al, 2008;Luethcke et al, 2011;Vasterling et al, 2012;Rosenfeld et al, 2013) and civilian (Bryant et al, 2010;Mayou et al, 2000) settings. Moreover, these findings have been corroborated using prospective study designs in civilians (Roitman et al, 2013) and in active duty service members (Yurgil et al, 2014).…”
mentioning
confidence: 99%
“…Although resilience is the most common outcome, as many as 20% of returning military personnel are affected with PTSD (Hoge et al, 2004). Further, approximately 15-20% returning service members reported a probable TBI during their deployment ((e.g., Belanger, Uomoto, & Vanderploeg, 2009;Tanielian & Jaycox, 2009;Terrio et al, 2009;Hoge et al, 2008;Schneiderman, Braver, & Kang, 2008;Vasterling et al, 2006). Thus, the recovery and reintegration of a significant minority of returning military personnel will be affected by these conditions.…”
mentioning
confidence: 99%
“…Among those who reported loss of consciousness, the incidence of PTSD was 43.9%, among those reporting altered mental status, it was 27.3%, and those reported other injuries, it was 16.2%. In contrast, those soldiers reporting no injury in combat, the incidence of PTSD was only 9.1% (Schneiderman et al, 2008). Because of likely common biochemical defects, as discussed in previous sections, it is not surprising that a direct relationship between mild TBI and PTSD exists.…”
mentioning
confidence: 99%
“…The relationship between mild TBI and PTSD has been reviewed in two recent epidemiologic studies of US soldiers returning from Iraq and Afghanistan (Hoge et al, 2008;Schneiderman et al, 2008). In one study on 2525 soldiers, 4.9% reported injury with loss of consciousness, 10.3% reported injuries with altered mental status, and 17.2% reported other injuries during deployment.…”
mentioning
confidence: 99%